Mitochondrial Diseases 2018
DOI: 10.5772/intechopen.80284
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction Associated with Doxorubicin

Abstract: Cancer prevalence is scaling up each year. Anthracycline groups are still the best chemotherapeutic agent. The most popular anticancer drug in the group is doxorubicin (DOX). Unfortunately, DOX has potent toxicity on noncancerous tissues, e.g., heart, kidneys, etc. However, it is well documented that the severest toxicity of the drug affects heart tissue. Of course, some reasons have been suggested why and/or how the heart is so vulnerable to toxicity. The primary mechanism responsible for DOX's cardiospecific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 88 publications
(381 reference statements)
0
13
0
Order By: Relevance
“…Hence, the volume of cardiomyocytes consists of 30-40% mitochondria [41]. As mentioned earlier, ROS production in the mitochondria is assumed to be the cause of mitochondria injury [42][43][44]. Doxorubicin has a strong binding affinity to cardiolipin in the inner membrane of mitochondria, that may directly cause the disturbance of the electron transport chain (ETC), which cause increased the ROS dan RNS [45][46][47].…”
Section: Mitochondria Injurymentioning
confidence: 99%
“…Hence, the volume of cardiomyocytes consists of 30-40% mitochondria [41]. As mentioned earlier, ROS production in the mitochondria is assumed to be the cause of mitochondria injury [42][43][44]. Doxorubicin has a strong binding affinity to cardiolipin in the inner membrane of mitochondria, that may directly cause the disturbance of the electron transport chain (ETC), which cause increased the ROS dan RNS [45][46][47].…”
Section: Mitochondria Injurymentioning
confidence: 99%
“…A crucial role of mitochondria to maintain accurate spermatogenesis involves the regulation of mitochondrial dynamics, which are defined by a balance of fission and fusion. Alteration of this balance causes changes in mitochondrial function, which is involved in the pathogenesis of some diseases (Marques‐Aleixo et al., 2018; Guven et al, 2018). It has been documented that enhances in the levels of ROS result in changes in the activity of the proteins involved in the mitochondrial dynamics (Cid‐Castro et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…DxR is a standard-of-care nonselective anthracycline molecule routinely used in the treatment of leukemia [ 21 ]. In this study, we demonstrated that Jurkat leukemia cells, if they are to survive a DxR assault, must quickly change mitochondrial morphology, rates of oxidative phosphorylation, and respiratory capacity.…”
Section: Discussionmentioning
confidence: 99%